Strategies and Efforts of Characterization by Mrs Latummahina in the Script Pelangi by Nano Riantiarno - Nazria, Nazria; Irianto, Ikhsan Satria; Bahar, Mahdi (Creativity And Research Theatre Journal, 2023)
This role creation work uses the concept of problem solving through strategy and effort. The strategy and efforts were applied to the character of Mrs Latummahina in the Pelangi script by Nano Riantiarno. The research method used is a descriptive-qualitative method which is based on analysis of the script, while the acting method used is the Stanislavski acting method. The findings from the creation of the character of Mrs Latummahina are that there are three acting strategies used, namely providing a script, understanding the character and acting the character. In order for the acting strategy to be achieved, the acting efforts chosen are script selection, script analysis, characterization analysis, designing acting concepts, applying acting methods, the process of creating roles and dressing actors.